2019
DOI: 10.2136/sssaj2018.12.0472
|View full text |Cite
|
Sign up to set email alerts
|

Methane Emissions from Estuarine Coastal Wetlands: Implications for Global Change Effect

Abstract: Core Ideas We investigated estuarine environmental factors on CH4 flux from two vegetation communities. Warming significantly affected on CH4 emission from the Phragmites australis community. There was a significant correlation between CH4 flux and water level in both communities. Salinity significantly affects CH4 emissions from the Phragmites australis community. The interaction between temperature and water level was the most important factor controlling CH4 flux. Global warming, rising sea levels, and salt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…This follows prior field, mesocosm, and incubation studies across a variety of wetlands, in which temperature has been shown to be a strong predictor of CH4 emissions (e.g. Al-Haj and Fulweiler, 2020;van Bodegom and Stams, 1999;Christensen et al, 2003;Dise et al, 1993;Fey and Conrad, 2000;Liu et al, 2019;Ward et al, 2013;Yang et al, 2019;Yvon-Durocher et al, 2014) and in which plant functional type has an interacting effect (Chen et al, 2017;Duval & Radu, 2018;L. Liu et al, 2019;Mueller et al, in press;Ward et al, 2013).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…This follows prior field, mesocosm, and incubation studies across a variety of wetlands, in which temperature has been shown to be a strong predictor of CH4 emissions (e.g. Al-Haj and Fulweiler, 2020;van Bodegom and Stams, 1999;Christensen et al, 2003;Dise et al, 1993;Fey and Conrad, 2000;Liu et al, 2019;Ward et al, 2013;Yang et al, 2019;Yvon-Durocher et al, 2014) and in which plant functional type has an interacting effect (Chen et al, 2017;Duval & Radu, 2018;L. Liu et al, 2019;Mueller et al, in press;Ward et al, 2013).…”
Section: Discussionmentioning
confidence: 83%
“…CC BY 4.0 License. functional groups and CH4 emissions have been demonstrated through field studies in other wetland ecosystems such as peatlands (Bubier et al, 1995;Ward et al, 2013) (Bubier et al, 1995, Ward et al, 2013) and in tidal wetland mesocosms (L. Liu et al, 2019;Martin & Moseman-Valtierra, 2017;Mueller et al, in press). We provide field evidence that two species with distinct plant traits --Schoenoplectus and Spartina --have strikingly different effects on CH4 emissions from brackish wetlands.…”
Section: Plant Traits Modify Warming Effects On Ch4 Cyclingmentioning
confidence: 96%
See 1 more Smart Citation
“…Measurements of Schoenoplectus, Spartina, and Distichlis biomass were conducted during peak biomass of each year (29 July-2 August) as described by Noyce et al (2019). Schoenoplectus biomass was estimated using non-destructive allometric techniques (Lu et al, 2016) in 900 cm 2 quadrats, and Spartina and Distichlis biomass were estimated through destructive harvest of 25 cm 2 subplots.…”
Section: Plant Biomass Measurementsmentioning
confidence: 99%
“…Recent research point to largely underestimated methane emissions from oil and gas production questioning also the lower GHG emission factor of natural gas [16]. Furthermore, models predict a strong increase of natural emissions such as from permafrost [17][18][19].…”
Section: Introductionmentioning
confidence: 99%